Metafilozofia, czyli o filozofii po filozofii (choć nadal z jej wnętrza) – na przykładzie refleksji historycznofilozoficznej Hegla i Heideggera - Gawlik, Cyprian (Człowiek i Społeczeństwo, 2022)
The main purpose of the paper is to characterize the metaphilosophical paradigm of today’s philosophy. The author argues that contemporary philosophical thought is thoroughly – and in a complex sense – metaphilosophical in nature. Namely, it takes the form of philosophy’s reflection on itself practiced after its end, but still from within philosophy. Understood in this way, metaphilosophy unifies the formal-spatial and temporal meanings of the prefix “meta-” as well as the two corresponding specific paradigms of metaphilosophy: philosophy of philosophy and post-philosophy. In order to substantiate this hypothesis, (1) the Hegelian historical-philosophical position, which marks the final moment of classical philosophy, is first presented, and on its basis the situation of contemporary thought, which is determined by the problem of the future of philosophy, is outlined. (2) Then the “early” and “late” philosophy of Martin Heidegger, which belongs to the metaphilosophical epoch of post-classical philosophy, is discussed. (3) This ultimately allows the author not only to draw conclusions about the condition of philosophy today, but also to outline an original context for a potentially fruitful confrontation between these two authors, which is the second aim of the paper.